Psak 22: Implementasi Akuntansi Kombinasi Bisnis (Studi Kasus Merger Pt Indosat Ooredo Tbk. Dengan Pt Hutchison 3 Indonesia) - Andriyanto Andriyanto; Fiya Zahrotunnisa; Endang Kartini Panggiarti (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
. Business mergers are carried out with many goals, including increasing company profitability and efficiency. This research contains the application of business combination accounting to the merger of PT Indosat Ooredo Tbk. with PT Hutchison 3 Indonesia with the implementation of PSAK 22. The aim of this research is to determine the impact of business combinations on company performance and income. The research method used is a literature study of journals, websites and previous articles. The results of this research include an overview of the application of business combination accounting and its impact on company performance and income. Through financial performance analysis carried out using ROA, ROE, PER and NPM, the results show a rapid increase after the merger of PT Indosat Ooredo Tbk. with PT Hutchison 3 Indonesia. This research encourages companies to maintain their achievements and maintain the trust of investors and customers.